Spanish Historiography and the Interregnum in Louisiana (1763-1803): a Case of (Voluntary) Amnesia? - Soizic Croguennec (Les Cahiers de Framespa)
For almost half a century, from the Treaty of Paris (1763) to the purchase of Louisiana by Napoleon (1800), this territory had been part of the Spanish colonial empire. However, this new, and ephemeral, possession never really became a central part of the Spanish historiography. The few allusions to the Interregnum are indeed associated to the terms and notions of failure, superficial and insufficient colonization, « poisoned gift »… Furthermore, the studies dedicated to this particular period and area are scarce, and very few were written in Spanish, by Spanish and Hispanic scholars, to the point one could be tempted to evoke a case of voluntary amnesia about the topic. In the Louisianan context, the very use of a term such as « Interregnum » to qualify this period reveals a common view that considers the Spanish presence in Louisiana as a mere transition. More generally, this intellectual attitude is thought provoking in the sense that it makes one wonder about how scholars tend to manifest a lack of interest for the failures of their national history.